Marketing de relacionamento: um estudo em uma cooperativa de crédito - Lamb, Chandler Mateus (2022)
The present work had the objective of presenting the motivating and inhibiting factors for the development of a long-term relationship in a credit union located in the southern region of the state of Rio Grande do Sul. The main motivating factors of the relationship are trust, commitment and responsibility. The main inhibiting factors of lasting relationships are lack of return, lack of trust and poor service. The work was based on relationship marketing and credit cooperatives. For this purpose, a qualitative exploratory research was carried out with ten associates and ten branch managers from October to November 2022.